PENGARUH LARUTAN ALKALI DAN YEAST TERHADAP KADAR ASAM, KAFEIN, DAN LEMAK PADA PROSES PEMBUATAN KOPI FERMENTASI - Nurul Hanifah; Desy Kurniawati (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2013)
Low-caffeine coffee currently produced in our country is very widespread, ranging from methods dekafeinasi, fermented animal luwak, wet methodsfermentationt have been developed in several coffee factory in Indonesia. According Pranoto Soenarto, Indonesia is the third largest coffee producer in the world after Brazil and Vietnam. It makes coffee as a commodity Pexport crops that have a relatively high economic value in the world market. The goal in this research is to make coffee with a balanced content, and good for the body. The method developed in this study is fermented with the addition of an alkaline solution method for the continued fermentation with yeast, which methods will be compared to the animal mongoose fermentation method, and wet fermentation methods. The results of the comparison is realized by comparing caffeine, acids, fats, and organoleptic. Methods adding lye and then do the fermentation by yeast is divided into several variables, fermentation by lye and long fermentation time. Based on the research conducted, it can be concluded that the presence of these three methods as variables changed significantly decreased the levels of acid, caffeine and fat content compared with standard, and fatty acids for the traditional coffee or regular processing. The low levels of acid fermenta caffeine tion is the method by animal mongoose, and yeast fermentation method and fermentation method followed by a wet, while acidity by fermentation of yeast, the addition of NaOH solution can significantly reduce the high acid, compared with the variable addition of other alkaline solutions. As for the caffeine, the caffeine content is low in the animal mongoose fermentation method, and then fermenting yeast and fermentation followed by damp. For the low fat content is the yeast fermentation method, to be followed by fermentation mongoose and wet fermentation. Meanwhile, by comparing the addition of alkali, NaOH variables are variables which contain acids, fats and caffeine are the lowest compared with the other variables. For variable length of fermentation time, 10 hours of fermentation is a variable length of time of fermentation is best, in a sense are optimal compared to 20 hours and 30 hours of fermentation.